Super-resolution electron ptychography of low dimensional materials at 30 keV: beyond the detector limit - Allen, CS; Danaie, M; Warner, JH; Batey, DJ; Kirkland, AI (AIP Publishing, 2023)
We demonstrate that electron ptychographic phase reconstruction can recover spatial frequencies higher than those directly recorded in the experimental electron diffraction patterns. This ability to recover high angle information from the oversampled low angle information allows an annular detector to be inserted which partially shadows a lower pixelated detector to simultaneously record a conventional annular dark field image and a ptychographic dataset. We apply this approach to 30 keV imaging of monolayer molybdenum disulfide and achieve an Abbe limited resolution of 1.2 ± 0.1Å in our reconstructions.